MEDIA SOSIAL DAN POLITIK MAHASISWA STUDI KASUS PENGGUNAAN MEDIA SOSIAL OLEH PENGURUS ORGANISASI INTRA KAMPUS DALAM INTERAKSI POLITIKNYA - Lendy Nurul Z; Priyatno H; Rina Martini (Journal of Politic and Government Studies, 2014)
The recent flowering of internet has resulted in the emergence of many online siteswhich facilitates its users to seek for information and communicate on different space anddistance. The obvious evidence of this internet flowering is the emergence of many socialmedia sites such as facebook, twitter, blog, instagram, and path which attract the society tobe actively involved and use it on their everyday life. Basically, all social media have thesame function and purpose that is to be used to communicate with other people. In Indonesiaitself, the biggest social media user is ranged between age 18 until 24 and mostly iscollegian. Collegian use social media for various purposes, such as for communicationbetween friends, for consolation purpose, also for political interaction. The problem that isexamined in this research is about the involvement of the internal organization committeecollegian of FISIP Undip about the usage of social media for their political interaction.According to that, the writer aims to analyze of how collegian use social media for thepurpose of political interaction. The following result is used to answer the question about thebackground of the collegian to make political interaction in social media. Research resultshows that social media is used more to their general information exchange and as theirentertainment purpose. Social media has not yet to be the main means in conducting politicalinteraction, but rather mere to be complementary. Collegian is not yet depended on socialmedia in getting the following political action, even though it is considered quite effective onthe usage. By far, social media becomes a medium of political interaction itself. It is advisedthat collegian can be actively involved in online network and is recommended to get morebenefit from the usage of social media, so that collegian can be more serious in order toimprove the political interaction.Keywords: social media, political interaction